Coupled plasmon resonances of Au thorn nanoparticles to enhance solar absorption performance. (July 2020) - Chen, Meijie; Wang, Xinzhi; Hu, Yanwei; He, Yurong
Highlights: Optical evolution of gold thorns was studied to improve its SPR peak. Enhanced absorption mechanism of gold thorns was discussed. This work provides design strategies toward new nanostructures. Abstract: To enhance solar absorption performance of nanoparticles in the solar thermal conversion applications, the optical behavior of Au thorn nanoparticles is studied numerically. A new design strategy toward new nanostructures is provided by coupling with the local surface plasmon resonances and propagating surface plasmon resonances in this work. Results show that Au thorn nanoparticles have the broad absorption region compared with Au sphere nanoparticles due to the multi-resonance peaks. Further study reveals that the enhanced absorption mechanism of Au thorn nanoparticles can be attributed to the propagating surface plasmon resonances along the thorn part, which is coupled with the surface plasmon resonance of the bulk sphere part. Geometry parameters (radius, length, thorn number) are also investigated to tune optical properties of Au thorn nanoparticles. Finally, solar absorption efficiency calculation shows that Au thorn nanoparticles can achieve the higher solar absorption performance with less particle consumption than Au sphere nanoparticles.